Nutritional Composition of Five Spontaneous Wild Plants Used as Human Foods in Côte d’Ivoire Areas (West Africa), a Potential Role in Household Food Security - Ehouan Ehile, Stephane-Joel; Kouassi, Nestor Kouakou; Kouame, Camille Adam; N'Dri, Denis Yao; N'guessan, Georges (Pakistan Journal of Nutrition, 2018)
Objective: The present investigation was undertaken to investigate the proximate, mineral, vitamin and phytochemical constituents of five spontaneous plant species widely consumed in Côte d’Ivoire: Solanum nigrum (Fouébrou), Ceratotheca sesamoides (Nanogo), Sesamum radiatum (Mangnrin), Abelmoschus tuberculatus (Kogogban), Myrianthus arboreus (Tikriti). Materials and Methods: Proximate values were determined according to standard methods and the energy content was calculated. Food plants mineral analysis was performed by atomic absorption spectrophotometric methods. The data were statistically analyzed. Results: Proximate composition of the plant foods samples ranged in 6.9-11.0% moisture, 11.0-13.3% ash, 14.6-19.5% crude fiber, 20.3-29.0% protein, 3.0-22.0% lipid, 34.0-55.3% carbohydrate and 331.0-430.3 kcal/100 g calorific values. Vitamin B9 and β-carotene compositions varied in 432.3-13480.0 and 0.2-0.4 mg/100 g, respectively. The elemental analysis of the six leaves in mg dry matter indicated that the leaves contained appreciable levels of potassium (1238-4228 mg/100 g), calcium (1058-2446 mg/100 g), magnesium (393-607 mg/100 g) and iron (0.3-0.8 mg/100 g). The antinutrient composition for phytic acid, oxalic acid and total polyphenols were ranged in 720-1300, 700-837 and 2012-8299 mg/100 g, respectively. The different ratios sodium/potassium (<1) and oxalates/calcium (<2.5) were under the respective critical value for all the species. Conclusion: These results revealed that these leaves can be used to combat micronutrient deficiency, also called "hidden hunger", a main cause of health problems and high mortality for groups at risk, mainly children and pregnant women in tropical Africa.